Analysis on Fees Exemption Policy of Land and BuildingRights Acquisition in Jakarta - Sonya Whisty Yogyandaru; Ima Mayasari (Universitas Padjadjaran, 2020)
The policy for imposing 0% (zero-percent) Land and Building Title Acquisition Fee in DKI Jakarta Province under Governor Regulation Number 126 of 2017 has been implemented for a period of 4 (four) years. In practice there have been found various advantages and weaknesses in the course of policy implementation. This study aims to describe the result of the evaluation on the implementation of the policy imposing zero-percent of Tax Object Acquisition Value (BPHTB). This study used qualitative descriptive method which suggests the explanation and understanding of the phenomenon in the grant of tax incentive. The outcome from the study reveals that the benefit from the policy is the ease of tax burden for the lower middle class communities to own house in DKI Jakarta and to encourage the acceleration of the land certification. The policy implementation also however implies that many taxpayers avoid the tax by using loophole in the Governor Regulation to enjoy this tax facility.